Probiotic mediated colonization resistance against E.coli infection in experimentally challenged Caenorhabditis elegans. (February 2019) - Sharma, Kavita; Pooranachithra, Murugesan; Balamurugan, Krishnaswamy; Goel, Gunjan
Abstract: This study investigates the antimicrobial potential of sixteen indigenous probiotic bacteria in Caenorhabditis elegans infected with different serotypes of clinical Escherichia coli isolates. The probiotic cultures exhibited varying degree of antimicrobial activity against the pathogenic strains. The Cell Free Supernatant (CFS) of Lactobacillus plantarum K90 exhibited maximum antimicrobial activity against all indicator strains. Further, the pathogenic potential of the clinical strains was determined using liquid killing assay in C. elegans, where the pathogenic strains resulted in complete killing of the worm in 5 days as compared to 60% survival of worms fed with standard food of E. coli OP50. The clinical strains also resulted in impaired pharynx and internal hatching of the eggs in the worms. The protective effects of probiotics against the pathogenic strains was determined via competition, exclusion and displacement assays with different stages of intervention of probiotic culture. No significant increase in mean life span (MLS) of the worm was observed in competition and displacement assay. Among the tested strains in exclusion assay, a pretreatment with L. gastricus BTM 7 was found to result in better protection of the worm against infection with pathogenic E. coli strains by extending its life by three days and no other adverse effect on physiology and morphology of the worm. The results suggest that preconditioning with probiotic strains can be used as an effective way to reduce the invasion and colonization by the pathogens. Highlights: Competitive exclusion assays were established in C. elegans model. Exclusion, displacement and competition assays were reported. E. coli serotypes limited the life span of the worm upto 6 days only. Pre-conditioning with probiotics resulted in extension of mean life span of infected worm.